Answer: LHS = RHS
Step-by-step explanation:
Heya!!
Here, we need to compare the LHS and RHS
So, here is the solution -
(9p-5q)²+ 180 pq = (9p+5q)
LHS
= (9p-5q)²+ 180 pq
= 81 p² + 25 q² + 90 pq + 180 pq
= (9p - 5q) ²
RHS = (9p - 5q) ²
Hence, proved => LHS = RHS
Hope it helps!
Step-by-step explanation:
-20+11
negative and positive sign will change in negative so ans will be=-9
because positive sign is on greater number
Answer:
2-9=x
HOW
let the number be x
then 2 less than product 9
so
2-9
and a number
we don,t know number so take it x
so 2-9=x
Answer: x^2 -10x + 24
Step-by-step explanation:
(x-6) (x-4)
= x^2 - 6x - 4x + 24
= x^2 -10x + 24
Answer:umm I think to do that you need to สะเดมแคพสพว เุ่ะมำงกรด พรพเ่พยวพ
Step-by-step explanation:ระะทืะยะะืะนะทะ ถระทพนดทเรทเสเยเสเรเาดยเสะมะนเสเร้าเสพ